The inclusion of the deaf person in higher education - Gómez Tovar, Rose Mery (Avances en Supervisión Educativa, 2013)
The research that is presented in this study is based on my experience with deaf students from the Psicology and therapist faculty of human communication which is an academic unit from the Juarez University of the Durango state. This article compiles and analyzes the process of inclusive and educational settings that the institution has.  This study is executed from the adoption of the analysis model of the biographic narrative investigation seen from the cualitative paradigm. In this project, the collected information is interpreted through the narrations, interviews, photo evidences and recordings make to the participants in order to give an appropriate response to the different objectives.
Keywords: inclusive education; inclusive environments; deaf people; higher education